Synthesis, Anticancer and Radioprotective Activities of Some New Pyrazolo[3,4-d]pyrimidines Containing Amino Acid Moieties - Ghorab, Mostafa M; Ragab, Fatma A; Noaman, Eman; Heiba, Helmy I.; Aboulmagd, Sarah A. (Arzneimittelforschung, 2009)
Various isomeric structural purine analogues possessing the pyrazolo[3,4-d]pyrimidine nucleus bearing amino acid moieties have been synthesized. The structures of the synthesized compounds were elucidated by spectral data. Preliminary testing for in vitro anticancer activity of the synthesized compounds against Ehrlich ascites carcinoma cells was carried out.2-(1-Phenyl-1H-pyrazolo[3,4-d]pyrimidin-4-ylamino)-propanoic acid (3b), 4-methyl-2-(1-phenyl-1H-pyrazolo[3,4-d] pyrimidin-4-ylamino)-pentanoic acid (3d), 4-methylthio-2-( 1-phenyl- 1H-pyra-zolo[3,4-d] pyrimidin-4-ylamino)-butanoic acid (3e) and phenyl-2-(1-phenyl-1H-pyrazolo[3,4-d] pyrimidin-4-ylamino)-propanoic acid (3f) were the most active compounds. Moreover, compounds 3e and 1-( 1-phenyl-1H-pyrazolo[3,4-d] pyrimidin-4-yl)-pyrrolidine-2-carboxylic acid (4) exhibited significant in vivo radioprotective activity.
Keywords: Anticancer agents; Pyrazolo[3,4-d]pyrimidines, amino acid side chains; anticancer activity, radioprotective activity, synthesis